Social Media Information Design Strategy In Increasing Sea Freight Sales (Case Study On Social Media Pt Yicheng Logistics Indonesia) - Agung Kwartama (International journal of technology and education research, 2025)
Social media has become an important tool in marketing and sales in various industries, including sea transportation. PT Yicheng Logistics Indonesia, as one of the major players in this sector, utilizes social media platforms to increase their visibility and sales. This study aims to analyze the information design strategy implemented on social media by PT Yicheng Logistics Indonesia and its impact on increasing sales. Using qualitative methods and analyzing data from various sources, this study found that informative and interactive content, the use of paid advertising, and active engagement with customers are key factors in the success of their marketing strategy. The results show that the right strategy in designing social media information can increase sales and strengthen the company's position in the sea freight market.